Design and implementation of intelligent question and answer system - Minh, Phan Cong (2015)
The aim of this project is to design and develop a Question and Answer (Q&A) system with students to be targeted users. Our Q&A system is called NTUAsk which is an interactive and extremely easy-to-use system that encourages Q&A between student and lecturer in Nanyang Technological University NTU). The new Q&A system is in hope to replace the traditional discussion forum in NTU Learn which is underused and not interactive. NTUAsk helps to break the barrier of hesitation by allowing student to ask question anonymously (i.e. a random retro avatar image will be used to represent user's identity instead of his real name). Beside the simple UI design focuses on easy of usage, NTUAsk also provides functions to engage users such as class reminder widget, o ine campus map. The design and development of the system include back end database design, python web server, front end web and android application interface. The system is designed in the way that is easy to adapt to multiple display platforms and changes in requirement. The system can be extended to usage of other schools/-colleges.